Determinant of Earnings Management Practices in Indonesia’s Consumer Goods Companies - Ardillah, Kenny; Vesakhadevi, Selvi (Universitas Negeri Semarang, 2021)
This research expects to decide the impact of tax planning, audit quality, and managerial ownership on earnings management. This information utilizes auxiliary information acquired from the organization's yearly financial report. The research populace is the manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange in 2016-2019. The research sample was taken with specific criteria using the purposive sampling technique. This study’s hypothesis testing uses multiple linear regression. The research results indicate that audit quality positively affects earnings management. Tax planning and managerial ownership do not affect earnings management. This research can be a source of information for business people to increase the existence of the audit committee to pay more attention to financial reporting information, primarily related to earnings in financial statements, to reduce the practice of earnings management.